Critical Historical Reading of the Law of Unequal Historical Evolution - Saad, Faisal (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
There are many views on the question of the logic and mechanisms of historical development of human society; visions and answers vary, to the extent of total conflict sometimes, on other issues that relate organically to the first question, perhaps the most prominent of which is the general picture of the historical evolution diagram, Sequentially spherical stages, as well as the question of the so-called nation or the multiple nations that alternately lead the ship of the evolution of human society in general. This is where the sharp contrast between the two theories of the so-called equal evolution and the unequal historical evolution as a problem from which the research begins and ends with emphasis on the credibility of the last thesis and on highlighting a large and dangerous part of the ideological manipulation and blindness of the first thesis. The latter, which is one of the moss serious thesis of Europeanorientalism and the pervasive wooden understanding of the original thought of​​ Marxist origin.